Association between mothers’ screening uptake and daughters’ HPV vaccination: a quasi-experimental study on the effect of an active invitation campaign - Venturelli, Francesco; Baldacchini, Flavia; Campari, Cinzia; Perilli, Cinzia; Pascucci, Maria Grazia; Finarelli, Alba Carola; Moscara, Luigi; Rossi, Paolo Giorgi (BMJ open, 2017)
ObjectivesIn Emilia-Romagna, the Human Papillomavirus (HPV) vaccination campaign started in 2008 offering free vaccines for 1996 and 1997 cohorts. Systematic active invitation was implemented for the 1997 cohort. Our study aimed at measuring the impact of the active invitation campaign on HPV vaccine coverage and on coverage inequalities in 11-year-old girls. Second, we evaluated the effect of the HPV vaccination campaign on participation in cervical cancer screening by mothers of target girls.MethodsWe collected information on vaccination status for girls residing in Reggio Emilia in 2008 and mothers’ screening history, before and after the 2008 vaccination campaign. Log-binomial regression models were performed to estimate Relative Risk (RR) and 95% confidence intervals (CIs) of being vaccinated as regarded citizenship, siblings, mothers’ education, marital status and screening history, stratified by birth cohort. We also calculated RR of receiving a Pap test after the vaccination campaign as regarded education, daughter’s cohort and mothers' decision to have their daughter vaccinated. Interaction between education and cohort in mothers overdue for Pap testing was calculated.ResultsVaccination coverage was 46.3% for the uninvited cohort (1046/2260) and 77.9% for the invited cohort (1798/2307). In the uninvited cohort, daughters’ vaccination showed association with mothers’ education (8 to 11 years of education vs. graduated mothers, RR 1.61 95% CI 1.14–2.28), citizenship (foreigners vs. Italians, RR 0.45 95% CI 0.37–0.56) and screening history (regular vs. non-participant; RR 1.72 95% CI 1.26–2.36). In the invited cohort, only a slight association with screening history persisted (regular vs. non-participant; RR 1.20 95% CI 1.04–1.40). Highly educated under-screened mothers of the invited cohort showed a higher probability of receiving a Pap test after the vaccination campaign period (RR 1.27 95% CI 1.04–1.56) compared with those not invited,ConclusionActive invitation could increase overall HPV immunisation coverage and reduce socio-demographic inequalities and the association with mothers' screening participation.